Genotypic sex determination in teleosts: Insights from the testis-determining amhy gene - Hattori, Ricado Shohei (2013)
The master sex-determining genes identified so far in fishes are clearly not conserved, as evidenced by several unrelated genes reported to play critical roles in sex determination. In this study, we reviewed the molecular process of sex determination in the Patagonian pejerrey Odontesthes hatcheri, an emerging model due to the recent discovery that a Y-chromosome linked, duplicated copy of the anti-Müllerian hormone gene, amhy plays a pivotal role in sex determination. A comparative analysis with other newly found sex-determining genes of teleost fish, DMY/dmrt1bY, sdY, amhr2, and gsdfY is performed and alternative ideas are proposed to explain the mechanism involved in the rise of various types of non-homologous sex-determining genes